2002
DOI: 10.2320/matertrans.43.1444
|View full text |Cite
|
Sign up to set email alerts
|

Energetics of Hydrogen States in SrZrO<SUB>3</SUB>

Abstract: The optimized geometries and formation energies of hydrogen in the perovskite-type oxide, SrZrO 3 , have been calculated using the density functional theory under the generalized gradient approximation (GGA). The stable hydrogen sites in the oxide are examined with special interests. It is shown that the hydrogen is tightly bound to an oxygen ion and located slightly outside the ZrO 6 octahedron in SrZrO 3 . The O-H bond orientates towards the second-nearest-neighbor oxygen ion, which induces large local displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…[28][29][30] For convenience of the present discussion, the results in the undoped, Y-doped and Al-doped SrZrO 3 are reproduced in Figs It is apparent from Fig. 12 that the Y-O bond order is smaller than the Zr-O bond order, but the Al-O bond order is larger.…”
Section: Local Geometry and Activation Energy For Protonmentioning
confidence: 56%
See 3 more Smart Citations
“…[28][29][30] For convenience of the present discussion, the results in the undoped, Y-doped and Al-doped SrZrO 3 are reproduced in Figs It is apparent from Fig. 12 that the Y-O bond order is smaller than the Zr-O bond order, but the Al-O bond order is larger.…”
Section: Local Geometry and Activation Energy For Protonmentioning
confidence: 56%
“…In our recent study, such local geometries around hydrogen and acceptor ion have been investigated by the first-principles density functional calculations. [28][29][30] By comparing the present study with the previous study, we can discuss the mechanism of protonic conduction in a qualitative way. As a result, some guiding principles for materials design will be obtained through the comparison.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…By comparing the optimized geometry around hydrogen in between the orthorhombic SrZrO 3 and the cubic SrZrO 3 , 29) it is found that the O-H bond length decreases from 0.1055 nm in the cubic phase to about 0.099 nm in the orthorhombic phase, whereas the Zr-H distance increases from 0.2187 nm in the cubic phase to about 0.23 nm in the orthorhombic phase. The orientation angle of O-H bond, increases from 12.9 in the cubic phase to about 40 in the orthorhombic phase.…”
Section: Hydrogen Site In Undoped Srzromentioning
confidence: 99%